Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Team Quiz di Kelas V SD Negeri 125 Tebingtinggi, Kabupaten Mandailing Natal - Maisyaroh Maisyaroh; Elfia Sukma (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2025)
This research aims to describe the improvement in integrated thematic learning outcomes using the team quiz model in class V of SD Negeri 125 Tebingtinggi. This research uses the classroom action method (PTK). This research uses qualitative and quantitative research which was carried out in 2 cycles, cycle I was carried out in 2 meetings and cycle II was carried out in 1 meeting. Data collection techniques include observation, tests and non-tests. The subjects of this research were teachers and all class V students at SD Negeri 125 Tebingtinggi. The results of the research showed that there was an increase in three research aspects, namely: (a) planning in cycle I obtained a score of 80.35% (B) increased in cycle II to 92.85% (AB), (b) implementation of learning aspects in cycle I teachers obtained a score 82.95% (B) while the student aspect received a score of 77.27% (C), increasing in the second cycle in the teacher aspect to 95.45% (B) and the student aspect also obtained a score of 95.45% (AB), (c ) student learning outcomes in cycle I obtained an average score of 78.26 (C) increasing in cycle II to 86.60 (B). Thus, it can be concluded that the Team Quiz model can improve student learning outcomes in class V of SD Negeri 125 Tebingtinggi.